Efficient production of a mature and functional gamma secretase protease - Khan, I.; Krishnaswamy, S.; Sabale, M.; Groth, David; Wijaya, L.; Morici, M.; Berger, I.; Schaffitzel, C.; Fraser, P.; Martins, R.; Verdile, Giuseppe (Nature Publishing Group, 2018)
Baculoviral protein expression in insect cells has been previously used to generate large quantities of a protein of interest for subsequent use in biochemical and structural analyses. The MultiBac baculovirus protein expression system has enabled, the use of a single baculovirus to reconstitute a protein complex of interest, resulting in a larger protein yield. Using this system, we aimed to reconstruct the gamma (γ)-secretase complex, a multiprotein enzyme complex essential for the production of amyloid-β (Aβ) protein. A MultiBac vector containing all components of the γ-secretase complex was generated and expression was observed for all components. The complex was active in processing APP and Notch derived γ-secretase substrates and proteolysis could be inhibited with γ-secretase inhibitors, confirming specificity of the recombinant γ-secretase enzyme. Finally, affinity purification was used to purify an active recombinant γ-secretase complex. In this study we demonstrated that the MultiBac protein expression system can be used to generate an active γ-secretase complex and provides a new tool to study γ-secretase enzyme and its variants.